Shockwave-Loading-Induced Enhancement of T c in Superconducting Bi2Sr2CaCu2O8+δ - Tiansheng Liu (Nature Portfolio, 2017)
Abstract We report a shockwave method for altering the properties of the superconductor material Bi2Sr2CaCu2O8+δ (Bi2212). We find that the superconducting transition temperature (T c) increases from 84 K for the pristine sample to 94 K for the sample treated at a temperature and pressure of ~1200 K and ~31 GPa, respectively. X-ray diffraction and transmission electron microscopy characterizations indicate that this T c enhancement arises from a phase transition from pristine Bi2212 to a mixture of superconducting Bi2212 and semiconducting Bi2Sr2CuO6+δ (Bi2201) during the shockwave treatment. The shockwave-treated sample exhibits n-type semiconductor properties (with an on-off ratio ~5), in contrast to the pure metallic pristine sample. Our study offers an alternative route for modifying the superconducting properties via a shockwave treatment. Furthermore, this method may provide a new approach for studying other temperature- and pressure-sensitive materials.